Pembuatan Briket dari Fiber Kelapa Sawit Berperekat Tepung Tapioka dengan Metode Pembakaran Biasa (Karbonisasi) - Istianto Budhi Rahardja; Cenda E. Hasibuan; Yudi Dermawan; St Nugroho Kristono (JURNAL CITRA WIDYA EDUKASI, 2021)
This research discusses briquettes making from palm fiber with tapioca starch adhesive by using the conventional burning method (carbonization). Briquettes can be used for household need as well as in other forms of alternative energy, and the alternative energy produced is expected to have quality and be made from renewable raw materials and have cheap economic value. Briquettes are solid fuel derived from organic waste. The purpose of this research was to determine the effect of multiple solvents on the physical properties and quality of the resulting briquettes. This research was conducted at the Chemical Laboratory of Palm Oil Polytechnic, Citra Widya Edukasi on 20202, 11th December – 2021, 9th August. The stages of the research ie: 1) cleaning and drying (12 hour oven at 105° C); 2) carbonization for ± 1.5 hours; 3) powder (sieve 60 mesh); 4) kneading 100 gr with 150 ml 200 ml and 300 ml solvent; 5) printing (paralon) D: 6.5 cm and h: 2.5 cm; and 6) testing of moisture content, ash content, burn time and burn rate. The result showed that in the 300 ml solvent, the resulting briquettes had a lower density than the other samples, and the weight of the briquettes produced in this sample was lighter, and also had large pores.